'We are "free range" prison officers', the experiences of Scottish Prison Service throughcare support officers working in custody and the community. (December 2020) - Maycock, Matthew; McGuckin, Kenny; Morrison, Katrina
Between 2015 and 2019, 41 throughcare support officers (TSOs) supported people serving short sentences leaving custody across 11 Scottish Prison Service establishments. The role of prison officers in the provision of throughcare in the community was an innovation in Scotland and represents a new approach to the long-standing challenges around supporting reintegration from custody. Drawing on data from semi-structured interviews with 20 TSOs, this article examines their reflections on their role, bringing attention for the first time to the front-line perspectives of those involved in this novel approach to throughcare. TSO's reflections revealed their growing awareness of the 'pains of desistance' and the challenges around reintegration, insights which had not been apparent to them in their prior work as officers working only in prison. The community 'place' of the TSO work also enabled a renewed awareness of the limits of rehabilitation within a prison and their own institutionalization after years of working in the custodial environment.